2017
DOI: 10.1186/s12870-017-0971-0
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast proteome response to drought stress and recovery in tomato (Solanum lycopersicum L.)

Abstract: BackgroundDrought is a major constraint for plant growth and crop productivity that is receiving an increased attention due to global climate changes. Chloroplasts act as environmental sensors, however, only partial information is available on stress-induced mechanisms within plastids. Here, we investigated the chloroplast response to a severe drought treatment and a subsequent recovery cycle in tomato through physiological, metabolite and proteomic analyses.ResultsUnder stress conditions, tomato plants showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 84 publications
4
70
0
Order By: Relevance
“…Crop Breeding, Genetics and Genomics 26 of 32 regulated for both genotypes (Figure 2). This protein was also reported as down-regulated in tomato plants [40] under stress drought.…”
Section: Discussionmentioning
confidence: 73%
“…Crop Breeding, Genetics and Genomics 26 of 32 regulated for both genotypes (Figure 2). This protein was also reported as down-regulated in tomato plants [40] under stress drought.…”
Section: Discussionmentioning
confidence: 73%
“…However, a decreased relative abundance of CB proteins was recorded in soybean seedlings under flooding stress (Hossain and Komatsu 2014). Furthermore, a decreased content of proteins associated with photosynthesis including photosystem components, such as CB protein in tomato (Tamburino et al 2017), and rice (Wang et al 2011), were observed in response to drought stress. Overall, a reduced photosynthesis activity and a low relative abundance of CB proteins lead to suppression of seedling growth under waterlogging stress.…”
Section: Alteration In Leaf Proteome Under Waterlogging Stressmentioning
confidence: 96%
“…Pure and intact wheat chloroplasts were isolated from 10 g of fresh leaves according to Tamburino et al with modifications [10]. All steps were carried out at 4°C.…”
Section: Chloroplast Isolationmentioning
confidence: 99%
“…A proteomic analysis following chloroplast isolation provides a promising approach for elucidating chloroplast-located protein regulation and its relationship with stress resistance [7,8]. Until now, the strategy of chloroplast proteomics has been employed to investigate the possible molecular regulatory pathways in response to biotic or abiotic stress in a variety of plants, such as the chlorosis mechanisms of Nicotiana tabacum leaves induced by viral infection [9], the response mechanism of tomato (Solanum lycopersicum L.) to drought stress and recovery [10], and the pathways associated with salt tolerance in Kandelia candel [11]. However, to the best of our knowledge, few studies have reported on the chloroplast proteomic analysis of wheat in response to drought stress, especially when an exogenous regulator is applied.…”
Section: Introductionmentioning
confidence: 99%